Examining the role of human perceptions during cetacean stranding response in New Zealand - Stockin KA; Pawley MDM; Jarvis RM; Boys RM (Elsevier Ltd, 2022)
Cetacean strandings often elicit significant media attention and public engagement. However, how human perceptions of such events may influence decision-making during strandings response is poorly understood. To address this, we undertook an online questionnaire targeting stranding relevant/interested parties in New Zealand, Aotearoa to understand perceptions around stranding events and response. Participants responded to questions and statements using the 5-point Likert scale to explore human perceptions and expectations of intervention, decision-making, animal welfare and survival prognosis during strandings. Responses were analysed based on level of experience and role at stranding events using descriptive and multivariate statistics. A total of 268 respondents completed the questionnaire; most stated that human intervention is necessary to assist animals during strandings. However, 43% of respondents indicated that they did not know what affect intervention may have on the animals. Notably, participants felt that human intervention was more likely to improve survival (26%) than welfare (19%). Importantly, experienced responders appeared more welfare complacent, prioritising survival for strandings response decision-making. Respondents from the legislative agency responsible for strandings in New Zealand, indicated that public sentiment may take precedence over welfare considerations when considering euthanasia. Our results highlight a disjunct between perceptions of welfare and survival, despite these variables being inextricably linked. This may be cause for concern in highly publicised strandings events where management decisions are more likely influenced by public sentiment. Comprehensive animal assessments that are informed both by animal welfare and survival prognoses are required to ensure the best outcomes for stranded cetaceans.
Keywords: Survival; Human intervention; Animal welfare; Mass strandings; Cognitive dissonance